2018
DOI: 10.1080/17482631.2018.1479586
|View full text |Cite
|
Sign up to set email alerts
|

There is more to life than risk avoidance – elderly people’s experiences of falls, fall-injuries and compliant flooring

Abstract: Purpose: Falls are the most common cause of injury in all ages and are especially difficult to prevent among residential care residents. Compliant flooring that absorbs energy generated within the fall, has been proposed as a measure to prevent fall-injury, however little is known regarding the implementation aspects in clinical settings. The aim of this study is to explore the experiences of falls, the risk of fall-injury, prevention in general and specifically compliant flooring as an injury preventative mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 30 publications
3
27
0
2
Order By: Relevance
“…Analysis of FPMI conversations with participants illuminated how perceptions of fall risks and fall prevention strategies were filtered through self‐identity to determine older adults’ response to fall prevention. Similar to other study findings, participants in this study were not likely to accept and engage in fall prevention activities that did not fit with their self‐identity (Gustavsson et al., 2018; McMahon et al., 2011; Whitehead et al., 2006). In addition, we learned that fear of falling, an important variable in fall prevention research and practice, continues to be an important variable to study, but represents one factor in determining how an individual may respond to fall prevention.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Analysis of FPMI conversations with participants illuminated how perceptions of fall risks and fall prevention strategies were filtered through self‐identity to determine older adults’ response to fall prevention. Similar to other study findings, participants in this study were not likely to accept and engage in fall prevention activities that did not fit with their self‐identity (Gustavsson et al., 2018; McMahon et al., 2011; Whitehead et al., 2006). In addition, we learned that fear of falling, an important variable in fall prevention research and practice, continues to be an important variable to study, but represents one factor in determining how an individual may respond to fall prevention.…”
Section: Discussionsupporting
confidence: 84%
“…Past studies indicate that emotions are an important aspect to consider for fall prevention. For example, fear related to falling among older adults is well documented (Gustavsson, Jernbro, & Nilson, 2018; Lee, Oh, & Hong, 2018; Whipple, Hamel, & Talley, 2018). Older adults often do not want to talk about fall prevention strategies (Clancy, Balteskard, Perander, & Mahler, 2015), resist fall prevention education, are reluctant to make necessary changes to prevent falls (Hill, Day, & Haines, 2014; McMahon et al., 2011; Whitehead, Wundke, & Crotty, 2006) and underestimate their risk of falling (Kiyoshi‐Teo, Northrup‐Snyder, et al., 2019; Kiyoshi‐Teo, Northup‐Snyder, et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…posición, haciendo que el paciente pueda tropezar fácilmente; esto incrementa el riesgo de caída y por tanto es fundamental extremar el cuidado dichos pacientes al tiempo que se hace énfasis en la necesidad de programas de educación que advirtan del riesgo adicional que se puede causar el uso de estos dispositivos (17,18).…”
Section: Discusión [T1]unclassified
“…El tener catéter venoso periférico también aumentó el riesgo de desarrollo de caídas, lo que concuerda con el estudio de Méndez (6).Dado que este tipo de dispositivo se usa con alta frecuencia en la atención habitual de los pacientes hospitalizados, es importante evaluar la pertinencia de su uso valorando otras opciones de tratamiento, pues con este no solo aumenta el riesgo de caídas, sino que de infecciones también. En este aspecto también es importante que se entrene al personal de salud, al paciente y a su familia sobre su manejo (17)(18).…”
Section: Discusión [T1]unclassified
“…A recent scoping review of flooring interventions involved a thorough search of the literature; however, it did not involve a critical appraisal or systematic synthesis 17. A systematic review of studies identified in the scoping review16 18–25 as well as more recent studies,26–31 will provide a more reliable basis for decision-making and identify the next steps for research.…”
Section: Introductionmentioning
confidence: 99%